A Study on Electrochemical Behaviour of Sodium Saccharin in an Aqueous Electrolyte Solution Using Cyclic Voltammetric Technique by a Nano-sensor - Radhi, Muhammed M.; Amir, Yousif K. A.; Ibrahim, Anfal I. (Current Topics on Chemistry and Biochemistry Vol. 2, 2022)
It aimed to identify the electrochemical properties of sodium saccharin in different electrolytes, using a nano-sensor of the chemical compounds taken by diabetic patients as a replacement for natural sugar. The cyclic voltammetric approach was used to investigate sodium saccharine in various electrolytes, employing a modified glassy carbon electrode (GCE) containing carbon nanotubes (CNT) as the working electrode (CNT/GCE). With the CNT electro-catalyst on the GCE surface, the redox current peaks of 0.01 mM sodium saccharine in 1 M Na2SO3 were shown to improve both redox peaks. The effects of different sodium saccharine concentrations, pH, and scan rates in Na2SO3 have been investigated. In the cyclic voltammetric cell, the nanosensor also demonstrated good dependability and stability towards chemical substances. Other electrochemical parameters were determined, such as the potential peak separation (Epa-Epc\(≈\)100 mV), the current ratio (Ipa/Ipc\(≈\)1) of the redox peaks and the cathodic-anodic reaction rate. The diffusion coefficient value was determined at different scan rates.